Transformasi Digital Dalam Sektor Kesehatan Kajian Literatur Untuk Mendukung Inovasi dan Efisiensi Layanan Kesehatan - Septiani Santoso, Fazila; Ramadhani, Putri Aulia; Amnamuchlisah, Dira; Purba, Sri Hajijah (PT. Alahyan Publisher Sukabumi, 2025)
Digital transformation in the healthcare sector has become a key driver in enhancing innovation and improving service efficiency. Technologies such as telemedicine, electronic medical records (EMR), artificial intelligence (AI), and big data-driven health applications have enabled healthcare providers to deliver faster, more accurate, and cost-effective care. This literature review examines the application of digital transformation in healthcare, focusing on its impact on innovation and efficiency. By analyzing recent studies, this review identifies various technologies that support significant changes in healthcare service delivery models. Furthermore, the paper discusses the challenges faced in the implementation of digital transformation, including infrastructure issues, regulations, and the digital divide. The findings are expected to provide valuable insights for policymakers, healthcare professionals, and researchers to further optimize digital technologies in improving healthcare service quality.